PERAN HUMOR DALAM MODAL SOSIAL - Nazaruddin Zainal; M. Ramli A.T.; Sawedi Muhammad (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study is to look at the other side of humor, meaning that besides producing fun, it turns out that humor can also bond and can even build social relations. The method used in the study was descriptive qualitative. The results showed that humor plays a role in shaping trust, norms and solidarity in groups. Humor as a social capital bonding in building social relations by being inward looking as an initial way of fostering trust and becoming glue in groups, then paving the way for faster growth with the ability to create strong networking. Humor as a bridging social capital in connecting members to one another. Indirectly humor creates more intense interactions involving all members. Humor can be a link to the creation of interactions between group members, so members can understand each other's characters. Humor also indirectly forms the norm in the form of habits interacting with the aggressive style of humor that is agreed upon by members and becomes an identity in the group. Third, the existence of good social relations between members created through humor can create networking to strengthen solidarity.